Kirchenbild und Kircheneinheit : Der dominikanische "Tractatus contra Graecos" (1252) in seinem theologischen und historischen Kontext - Riedl, Andrea (2020)
The book focuses on the "Tractatus contra Graecos" (1252) by an anonymous Dominican from the convent of Constantinople, a theological dossier outstanding with regard to its various interaction with contemporary Latin-Greek discourses. Polemical theology is, to a certain extent, always making of: Notions of the other church are conveyed, which - if they did not meet their own expectations of the question of church unity - turned from the partner to the enemy. The analysis of these notions shows that under an often polemical text surface there is sometimes a much more original theology than one would expect this genre of text to be, and this theology is the central leitmotif of this book, drawing out and working into the sketch of medieval ecclesiology.